A Z-scheme heterojunction of ZnO/CDots/C3N4 for strengthened photoresponsive bacteria-killing and acceleration of wound healing. (15th November 2020) - Xiang, Yiming; Zhou, Qilin; Li, Zhaoyang; Cui, Zhenduo; Liu, Xiangmei; Liang, Yanqin; Zhu, Shengli; Zheng, Yufeng; Yeung, Kelvin Wai Kwok; Wu, Shuilin
Abstract: The abuse of antibiotics is leading to the emergence of resistant bacteria. In this work, a drug-free composite of ZnO/CDots/g-C3 N4 with Z-scheme heterojunction was developed, which was employed to kill bacteria effectively within a very short time under the irradiation of visible light due to the enhanced photocatalytic and photothermal effects. In this system, the CDots acted as a bridge between g-C3 N4 and ZnO, effectively inhibiting the recombination of photo-generated electrons with holes and consequently enhancing the photocatalytic properties. In addition, CDots endowed the system with excellent photothermal effects. As a result, the antibacterial efficacy of ZnO/CDots/g-C3 N4 composite against S. aureus and E. coli reached up to 99.97 % and 99.99 % respectively, after 15 min of visible light irradiation, due to the synergistic action of photo-inspired radical oxygen species and hyperthermia. The Zn ions released from the composite promoted the growth of fibroblasts, which accelerated the wound healing process.